THE IMPACT OF COVID-19 PANDEMIC ON THE ECONOMIC ACTIVITY OF PURSE SEINE FISHERMAN IN BANABUNGI VILLAGE, KADATUA DISTRICT, SOUTH BUTON REGENCY - Azwar Sidiq; Nurhuda Annaastasia; Abdul Sarifin; Yusnita Yusnita (Jurusan Perikanan dan Kelautan, 2021)
Fisherman are a group of people who are highly dependent on the fisheries resources in their efforts to fulfill their basic needs and to be a prosper. The outbreak of the Covid-19 not only threatens people’s lives and safety, but also has a significant impact on economic development both of which are macro and micro to be weakened. This research aims to determine the impacts of the Covid-19 Pandemic on Fishing activities, incomes, and marketing activities of purse seiner. The research was conducted on October 2020 in the Banabungi Village, Kadatua Subdistrict, South Buton Regency, Southeast Sulawesi Province. The results show that the impact of the Covid-19 has affected purse seiner’s fishing activities where production costs have increased by 4,62%, The of crews (ABK) have increased by 19,69%, and marketing at channel I (Producer-Wholesale)stopped. Consequently, where the change in fish price at fishemen level by 79,75%. The margin of marketing at channel II at wholesale level is IDR 5.556/kg. Meanwhile, at retail level is IDR 8.267/kg. Production was decreased by 79,93%, revenue decreased by 64,06% and profit decreased by 68,26% with value of R/C ratio 3.70 >1. The fishing location of fishermen has not change as in the previous year. Marketing volume during the peak fishing season is 14.809kg/month.